(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
According to a report, the statistical analysis of the drivers of terrorist activity show there are two distinct sets of factors associated with terrorism (depending on whether the country is developed or developing), i.e. the political violence committed by the state and the presence of a conflict. (Institute for Economics Peace 2016) According to the research findings, 93 per cent of all terrorist attacks between 1989 and 2014 occurred in countries with high level of state sponsored terror, involving extrajudicial killing, torture and imprisonment without trial while over 90 per cent of all terrorist deaths occurred in countries already engaged in some form of conflict whether internal or international. (ibid.) This means that only 0.5 per cent of terrorist attacks occurred in countries that did not suffer from conflict or political terror. (ibid.) This underlines the close link between existing political violence and terrorist activity.